2012
DOI: 10.1111/j.1755-0998.2012.03127.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular approaches identify known species, reveal cryptic species and verify host specificity of Chinese Philotrypesis (Hymenoptera: Pteromalidae)

Abstract: Philotrypesis, a major component of the fig wasp community (Hymenoptera: Pteromalidae), is a model taxon for studying male fighting and mating behaviour. Its extreme sexual dimorphism and male polymorphism render species identification uncertain and in-depth research on its ecology, behaviour and other evolutionary topics challenging. The fig wasps' enclosed habitat within the syconia makes their mating behaviour inaccessible, to the extent of matching conspecific females and males. In this study, we combine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 39 publications
(88 reference statements)
0
35
0
Order By: Relevance
“…None of the currently used nuclear markers achieve the widespread utility of favoured mtDNA markers like COI and cytb. However, an internal transcribed spacer region (ITS2) of rDNA has recently been proposed as a useful nuclear barcoding marker for animals [41-44]. …”
Section: Introductionmentioning
confidence: 99%
“…None of the currently used nuclear markers achieve the widespread utility of favoured mtDNA markers like COI and cytb. However, an internal transcribed spacer region (ITS2) of rDNA has recently been proposed as a useful nuclear barcoding marker for animals [41-44]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed within Ficus , intra-specific fig size variation is widespread and is spatially structured in at least some species [21, 22]. More generally, in many plant species, the size of some organs or structures, for instance the size of acorns [17], varies geographically and provides a series of situations in which processes analogous to the one documented here could apply.…”
Section: Discussionmentioning
confidence: 99%
“…Seven published Philotrypesis COI sequences, 3 from Hainan Island and 4 from Fujian were also included in the analysis [22, 23]. We built COI neighbor joining trees for the two genera.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been introduced into Brazil, Florida, Puerto Rico, and Hawaii (Beardsley, ; Farache et al , ; R. Wang and S. G. Compton, unpublished). This species may also utilise another fig tree host, Ficus benjamina L. (Zhou et al , ). Little is recorded about its biology, other than that females were observed to oviposit into figs that had been pollinated weeks earlier, which suggested that it may be a parasitoid, because gall‐forming species usually oviposit earlier (Compton, ; Chen et al , ).…”
Section: Methodsmentioning
confidence: 99%